The Restructuring of South American Soy and Beef Production and Trade Under Changing Environmental Regulations. (September 2019) - le Polain de Waroux, Yann; Garrett, Rachael D.; Graesser, Jordan; Nolte, Christoph; White, Christopher; Lambin, Eric F.
Highlights: South American countries have stepped up deforestation regulations and enforcement. We study potential spillover effects of these regulations for soy and beef. We find little change in soy or pasture expansion patterns due to increased regulations. We find a decrease in beef imports from more regulated biomes. Substitution between markets and actors diminish the effectiveness of regulations. Abstract: In response to the extensive loss of forests caused by soy and cattle expansion in South America, several countries have increased their legal restrictions on deforestation, and stepped up their enforcement. In addition, in the Brazilian Amazon, new private agreements were initiated in 2006 and 2009 to limit the purchase of soy and cattle linked with deforestation. One concern is that such policies, because they are spatially heterogeneous or focus on a subset of relevant actors, might generate negative spillovers in the form of leakage of agricultural activities and deforestation to less-regulated areas, and/or a redistribution of non-compliant product sales to non-participants. In this study, we use panel data on soy and beef production and trade in agricultural frontiers of South America to examine how changes in deforestation regulations in South America have altered soy and cattle expansion and exports in this region, and to understand how these changes, if they have occurred, influence the overall effectiveness of deforestation regulations. We find no evidence of a change in soy or pasture area expansion patterns due to changes in regulations, except within the Amazon biome where pasture expansion slowed in response to more stringent regulations and coincided with pasture intensification. We do find, however, a decrease in beef imports from biomes with more stringent deforestation regulations. While this decrease may indicate the existence of leakage to countries outside the study area, it is likely offset by pasture intensification, continued opportunities for deforestation, and increasing domestic consumption from these biomes. These results point to the potential role of substitution effects between local and international consumer markets, and between different actors, in diminishing the overall effectiveness of deforestation regulations.